Public-Private Partnership: Ghanaian Perspective of Urban Water Supply - Andani Mohammed, Adam; Mpawenimana Saidi, Abdallah (International Journal of Engineering and Technology, 2018)
In Ghana, tariff of utilities including water is put below cost recovery levels such that government is unable to cope with the challenges in water supply. As such, the government resorts to private partnership to fund the gaps in the urban water supply in the country. The study adopted an integrative multi-stage critical review of relevant literature on public-private partnership in urban water supply. As such articles published between 2006 and 2017 were selected by specific inclusion criteria. Relevant articles on the topic were identified through references and citations. The paper examines the status and trend of water supply, reforms and management of urban water supply in Ghana. The study found problems like poor water supply system, inadequate human and economic resources as well as poor resource allocations and urban water management.Â